Applying INCOSE Rules for writing high‐quality requirements in Industry. Issue 1 (13th September 2016) - Fuentes, Jose; Fraga, Anabel; Génova, Gonzalo; Parra, Eugenio; Alvarez, Jose María; Llorens, Juan
Abstract: The present paper introduces an implementation of some INCOSE guidelines for writing high‐quality requirements in industry, it presents the benefits of applying techniques, methods and tools in order to improve the Systems Engineering Process. It is also proposed an evaluation of the impact in the quality of requirements.